The effect of traditional strength training on sprint and jump performance in 12- to 15-year-old elite soccer players: A 12-month controlled trial - Skratek, J.; Kadlubowski, B.; Keiner, M. (The Journal of Strength and Conditioning Research, 2024)
The aim of the study was to evaluate the effect of traditional strength training on maximum strength (1 repetition maximum in front squat [FS] and back squat [BS]), jump (squat and countermovement jump), and linear sprint (LS) performance (5, 10, and 30 m) in elite young soccer players. A 12-month longitudinal design was chosen, and 48 elite male youth soccer players (age: 12-15 years) were included. The subjects were divided in 2 groups (a strength training group [STG] and a control group [CG]). The intervention group trained for 1 year over a competitive soccer season with additional sessions to their regular soccer practice (4 sessions per week), while the CG did not complete any additional sessions to the regular soccer training (4 sessions per week). The additional strength training (2 sessions per week [each approximately 30 minutes]) consisted of either parallel FS or BS. The squat variants switched in each session. Data were analyzed using a 2 × 3 (group × time) repeated-measures analysis of variance. The main findings of this study were that the STG resulted in significant pretest and post-test improvements in maximum strength (d = 3.75-5.58), jump (d = 0.84-1.14), and LS performance (d = -0.25 to 0.44), while for the CG, smaller increases or performance decreases were measured (maximum strength: d = 1.64-2.7; jump: d = 0.12-0.31; sprint: d = 0.00-025). A significant interaction effect in all variables indicated significant (p < 0.05) stronger performance improvements compared with the CG. Traditional strength training in elite youth soccer players is recommended to increase strength and speed-strength (jump and sprint performance) and should be considered in long-term athletic development programs.